Presence and diversity of mixed avian Plasmodium spp. infections in introduced birds whose distribution overlapped with threatened New Zealand endemic birds. Issue 2 (3rd March 2020) - Schoener, ER; Tompkins, DM; Parker, KA; Howe, L; Castro, I
ABSTRACT: Aims: To determine the presence of infection and co-infection of Plasmodium lineages in introduced birds at translocation sites for the North Island saddleback ( Philesturnus rufusater ), to investigate their role as Plasmodium spp. reservoirs. Methods: Blood samples were collected from introduced bird species, with a special focus on blackbirds ( Turdus merula ) and song thrushes ( Turdus philomelos ), at six locations in the North Island of New Zealand that were the origin, or translocation sites, for North Island saddleback. Where available, blood smears were examined, and blood samples were tested using nested PCR with subsequent sequence analysis, for the presence of Plasmodium spp. Results: Of the 55 samples tested using PCR analysis, 39 (71%) were positive for Plasmodium spp., and 28/40 (62%) blood smears were positive for Plasmodium spp. Overall, 31 blood samples were from blackbirds with 28/31 (90%) samples positive for Plasmodium spp. Six distinct avian Plasmodium lineages were identified, including three cosmopolitan lineages; Plasmodium vaughani SYAT05 was detected in 16 samples, Plasmodium matutinum Linn1 in 10 samples and Plasmodium elongatum GRW6 in eight samples. Mixed infections with more than one lineage were detected in 12 samples. Samples from two Australian magpies ( Gymnorhina tibicen ) were positive for Plasmodium . sp. lineage MYNA02, previously not identified in New Zealand. Conclusions and clinical relevance: This is the first report from New Zealand in which specific Plasmodium spp. mixed infections have been found in introduced birds. Co-infections with several cosmopolitan Plasmodium lineages were identified, as well as the first report in New Zealand of an exotic avian Plasmodium sp . lineage, in Australian magpies. Whilst the role of introduced birds in maintaining and spreading pathogenic avian malaria in New Zealand is unclear, there is a potential infection risk to native birds, especially where distributions overlap.